Fastenings for seismic retrofitting : state of the art report (Thomas Telford, 1997)
Since the mid-1970s advances in the various techniques for seismic retrofitting have been made and put into practice. This report reviews and introduces the latest design concepts and methods throughout the world, with emphasis on the use of fastening systems.